A world upside down: the carnival in Emilia Pardo Bazán and Mercè Rodoreda - Chalian, Marisol; Jersonsky, Eva (Revista Melibea, 2025)
In the present paper we will focus on the figure of Carnival in the works of two authors that come from the peripheric Spanish nations, separated by several decades: Emilia Pardo Bazán and Mercè Rodoreda. Based on the ideas that Bajtin ([1965] 2003) proposes regarding this trope -like its freedom, counter-hegemonic character and the elimination of borders-, our approach -following Tseëlon (2003)-will concentrate in the implications and possibilities that this extraordinary event opens for the female gender, not only because of the potential removal of borders and role inversion but also for the presence of disguises and masks that grant anonymity to the woman that attends the festivities and allow her to express and channel desires that are usually forbidden. In this way, analyzing specifically two short stories: “Los dominós de encaje” (1897), by the Galician author, and “Carnaval” (1958), by the Catalan author, we will try to unravel the journey of a topic not at all unfamiliar to the Iberic tradition that keeps on appearing with the passage of time, especially in regard to the questioning and the reflection about gender roles and women’s place in the public sphere.